PENGARUH PENGETAHUAN PRODUK DAN NORMA RELIGIUS TERHADAP SIKAP KONSUMEN DALAM NIAT MENGKONSUMSI PRODUK MAKANAN DAN MINUMAN HALAL (Studi Kasus di Kota Semarang) - Al Rochmanto, Bayu; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
This research is motivated by growth of food products and beverages in Indonesia in general and specifically in the city of Semarang, which are imported from non-Muslims countries, such as China, Thailand, the United States and Japan. Many products of food and beverages are categorized subhat, or are still doubt in halal. It wasfounded by many goods in several market in Semarang without halal license byauthorizedinstitution in Indonesia. Purpose of this study is to analyze and provide empirical evidence whether the product knowledge and religious norms have positive effectÂ  on consumer attitudes in the intention to consume halal food products and beverages in Semarang.This study uses multiple linear regression analysis using SPSS version 21. Data obtained by questionnaires and distributed to the Muslim community in Semarang who able to make own decisions to buy food and beverage products. 200 respondents has been collected with purposive sampling method.Result of this study showed that the product knowledge religious norms and consumer attitudes towards halal products have positive effect and significant on the intention to consume halal food products and beverages with the regression result Y2 = 0,266X1 + 0,149X2 + 0,325Y1.